Development of AHP Decision Model for Facility Location Selection in Malaysia - Tan, Meng Han (IRC, 2018)

(untitled)
An Analytical Hierarchy Model also known as AHP Model is a model that is being used to elicit the preference choices of the decision maker. An AHP Model are commonly used in decision making process which involves a large amount of complex and subjective factors. The AHP Model is capable to quantify these factors into different level of hierarchy and allocated weightage for each of these factors. The main objective of the project is to develop an AHP Decision Model for facility location selection amongst Automotive Industry and also to discover the important location factors that affect the process of decision making. The scope of study for the project will mainly be focusing on the Automotive Industry location selection in Malaysia. In depth research on the AHP Model and the location factors for Automotive facility location selection has been made and the formula and calculation for the AHP Model have also been discovered. In the result, we are able to develop a functional AHP Model that is capable of prioritizing the location factors that are chosen by the decision maker and determine the consistency of the decision made. The AHP Model in Excel are mainly divided into three sections which is the Input, Solution and Output, the input are required to be field by the decision maker while the output are calculated during the solution phase.